TRANSITIVITY ANALYSIS OF STUDENTS’ RECOUNT TEXTS - Elsie, Kadek Fredina; Adnyani, ni luh putu sri; Suarnajaya, I wayan (Jurnal Pendidikan Bahasa, 2020)
This study aimed at identifying the process types that characterize the students’ recount texts, identifying the process types which are dominantly used, and identifying the circumstantial elements that characterize the students’ recount texts. This study applied a descriptive qualitative method with a case study research. The recount texts written by class XI Usaha Perjalanan Wisata (UPW) 2 at SMK Wira Harapan were used as the sources of data collection of the study. There were 26 students taken as the subjects of the study. The data of the study which are in the form of sentences and clauses were analyzed based on transitivity system, and the problems experienced by the students in writing the recount texts were discussed through focus group interview in order to determine whether the students made mistakes or errors in their texts. The study discovers that, first, the process types that characterize the students’ recount texts are material process, intensive attributive process, mental process, circumstantial attributive process, verbal process, possessive attributive process, intensive identifying process, existential process, circumstantial identifying process, and behavioral process, which respectively appears 566 times (60.66%), 149 times (15.97%), 100 times (10.72%), 35 times (3.75%), 29 times (3.11%), 21 times (2.25%), 17 times (1.82%), 9 times (0.96%), 4 times (0.43%), and 3 times (0.32%). Second, the process type which is dominantly used in the students’ recount texts is material process with the frequency of occurrence of 565 times (60.82%). The material process was used dominantly since the topics written by the students were related to past activities. Third, the circumstantial elements characterizing the students’ recount texts are location, cause, manner, extent, accompaniment, matter, and role. The results of the focus group interview and the text analysis show that the students made many mistakes and errors in their recount texts, such as the uses of past tense, article, spellings, modal auxiliary, capital letter, plurality, and preposition in a clause. The two aspects leading the deviations are interlingual and intralingual errors.